Intersectionality - Hill Collins, Patricia 1948- (Key concepts, 2020)
"In this fully revised and expanded second edition of their popular text, Hill Collins and Bilge provide a much-needed introduction to the field of intersectional knowledge and praxis for students new to the field"--